Orientation and density control of bispecific anti-HER2 antibody on functionalized carbon nanotubes for amplifying effective binding reactivity to cancer cells. Issue 14 (18th March 2015) - Kim, Hye-In; Hwang, Dobeen; Jeon, Su-Ji; Lee, Sangyeop; Park, Jung Hyun; Yim, DaBin; Yang, Jin-Kyoung; Kang, Homan; Choo, Jaebum; Lee, Yoon-Sik; Chung, Junho; Kim, Jong-Ho
Abstract : Controlling the orientation and density of an antibody on carbon nanotubes leads to the sensitive detection of cancer cells. Abstract : Nanomaterial bioconjugates have gained unabated interest in the field of sensing, imaging and therapy. As a conjugation process significantly affects the biological functions of proteins, it is crucial to attach them to nanomaterials with control over their orientation and the nanomaterial-to-protein ratio in order to amplify the binding efficiency of nanomaterial bioconjugates to targets. Here, we describe a targeting nanomaterial platform utilizing carbon nanotubes functionalized with a cotinine-modified dextran polymer and a bispecific anti-HER2 × cotinine tandem antibody. This new approach provides an effective control over antibody orientation and density on the surface of carbon nanotubes through site-specific binding between the anti-cotinine domain of the bispecific tandem antibody and the cotinine group of the functionalized carbon nanotubes. The developed synthetic carbon nanotube/bispecific tandem antibody conjugates (denoted as SNAs) show an effective binding affinity against HER2 that is three orders of magnitude higher than that of the carbon nanotubes bearing a randomly conjugated tandem antibody prepared by carbodiimide chemistry. As the density of a tandem antibody on SNAs increases, their effective binding affinity to HER2 increases as well. SNAs exhibit strong resonance Raman signals for signal transduction, and are successfully applied to the selective detection of HER2-overexpressing cancer cells.